Relasi Gender dalam Pembagian Kerja dan Dinamika Adaptasi Musim pada Komunitas Pesisir Desa Sei Nagalawan - Farid Aulia (Inovasi, 2023)
Conditions related to the management of mangrove forests are part of the traditions of coastalcommunities with local designations for each type of existing activity. This activity is part of thelife cycle of coastal communities who work as fishermen. The gender relations formed are anadaptation to the changing seasons according to the Islamic calendar. Gender relations are part ofthe division of labor between men and women who interact with mangroves and the sea. NagalawanVillage has succeeded in carrying out cultivation activities and managing mangrove ecosystems asan ecotourism area. The Sei Nagalawan Village community has overcome seasonal dynamics byutilizing mangroves as a source of income as a subside of the limitations of fishing. This paperreveals the division of labor between men and women in the coastal community of Sei NagalawanVillage which shows gender relations in the division of labor and their local knowledge system.Changes in weather and seasons are important indicators in daily activities. Revealing its life cycle,it will also be known the span of time allocated to work. The method used qualitatively byconducting in-depth interview techniques and field observations. Field findings show thatadaptation to the season can influence gender relations that are formed in the socio-cultural life of coastal communities in Sei Nagalawan Village. Knowledge of the tides and seasons is alwaysassociated with the Hijri calendar in Islam.Keywords: dynamics of adaptation, division of work, utilization of mangroves, coastalcommunities